ANALISIS KARIOTIPE DAN PERTUMBUHAN KACANG KEDELAI (Glycine max L.) SETELAH DIINDUKSI SINAR ULTRAVIOLET - Rani Ernita Limbong; Elimasni D; Isnaini Nurwahyuni (Saintia Biologi, 2013)
“Karyotype and Growth Analysis of Soybean (Glycine max L.) after Exposed by Ultraviolet light” has been done at Genetic and Molecular Biology Laboratory at Natural Scienes Faculty and the greenhouse at Agriculture Faculty Sumatera Utara University Medan. The objective was to investigate design karyotype and vegetative growth of soybean that induced by UV light. The experimental design was used complete factorial randomized with 2 factors. The first are Ultraviolet (UV) light 3 levels : 10, 20 and 30 Watt and the second is the time of UV exposure with 3 levels : 5, 10, and 15 minutes. Each treatment replicates 2 times and plant that not exposed by UV used as control. The karyotype was observed by squash method. The results showed that the intensity and duration of UV light have no effect on the number of chromosomes but the light has effect on the number of chromosome type. Statistical analysis showed that the increase in UV energy up to 30 Watt and time exposure of 15 minutes, caused the increase in height, number of leaves, number of flowers, the fresh and dry weight of the plant, and chlorophyll concentration compared to untreated plants. Keywords: karyotype, mutation, soybean, ultraviolet.